Surgical Management of Skull Base and Spinal Chordomas: A Systematic Review and Meta-Analysis: Head Surgical Management of Skull Base and Spinal Chordomas - Daniel Encarnacion-Santos; Gennady Chmutin; Chmutin, Egor; Pachev, Murat; Eromanga, Baranico; Nazmin Ahmed (Iraqi Journal of Cancer and Medical Genetics, 2025)
Background: Chordomas are rare tumors originating from residual chordate tissues, predominantly affecting the base of the skull and the axial skeleton. Aim: This systematic review investigates the anatomical aspects and neurosurgical treatment modalities of skull base and spinal chordomas. Methods: We conducted a systematic literature review, adhering to PRISMA guidelines, by searching Databases including PubMed/Medline, Scopus, ScienceDirect, and EBSCO. Data was managed using Microsoft Excel and analysis was performed using SPSS Statistics for Windows, version 26.0 (IBM Corp., Armonk, NY, USA). PROSPERO Registration Number; CRD420261322007. Results: In this study, we conducted a systematic review and meta-analysis, including a total of N=2,083 patients with clinical and neurological manifestations, as outlined between Table I and Table IV. The analysis results are summarized in Table 1. N=1,485, (71.5%) patients, N=636, Gross total resection (GTR), N=640, subtotal resection (STR), N=568, Radiotherapy, as detailed in Tables I and II and Figures 1, 2, and 3. Heterogeneity was assessed as follows:  I² = [23%, 24%, 32%]. P = 0.21. Conclusion: The aggressive nature of chordomas necessitates personalized treatment strategies. Surgical approaches, particularly for elderly patients, proved promising in chordoma excision. Despite advancements, further research into disease management and etiopathogenesis is crucial for improved prevention, detection, and treatment strategies. Adjuvant therapies exhibited enhanced survival rates, highlighting their significance in prolonging patients' lives post-surgery.